Detecting people at high risk of type 2 diabetes- How do we find them and who should be treated?. Issue 3 (June 2016) - Kong, Alice P.S.; Luk, Andrea O.Y.; Chan, Juliana C.N.
Abstract : Diabetes is a chronic disease characterized by its silent and progressive nature. The prevalence of type 2 diabetes (T2DM) increases with age but with a worrying trend of increasingly young age of diagnosis. Compared to their counterparts with late onset of disease, these younger subjects face long disease duration with increased risk of diabetes-related complications. Besides, there is marked phenotypic heterogeneity which can interact with different interventions to give rise to variable clinical outcomes. Recognized at-risk groups include those with known atherosclerosis and vascular disease, genetic background (family history and non-White ethnic groups), phenotypes of insulin resistance (obesity, metabolic syndrome, women with gestational diabetes or polycystic ovarian syndrome, and men with androgen deficiency) and "pre-diabetes" (impaired glucose tolerance and impaired fasting glucose). These risk factors interact to amplify the risk for diabetes, thus emphasizing the importance of comprehensive assessment. Raising awareness and health literacy, regular screening of high risk subjects, structured lifestyle modification program including early use of pharmacological agents, targeting at predominant pathophysiological defects offers a personalized approach to prevent this global hazard.